Dietary Magnesium Intake Affects the Association Between Serum Vitamin D and Type 2 Diabetes: A Cross-Sectional Study - Huang, Weichao; Ma, Xiaoman; Liang, Hualiang; Li, Haojia; Chen, Jiayu; Fang, Liujia; Yang, Qilin; Zhang, Zhenhui (Frontiers in Nutrition, 2021)
Abstract Introduction: Circulating vitamin D concentrations have been associated with the risk of type 2 diabetes (T2D). However, the effect of dietary magnesium intake on the association between vitamin D and the risk of T2D has not been fully studied. Therefore, we designed this cross-sectional study to assess the effect modification of magnesium intake on the association of vitamin D and risk of T2D. Research design and methods: The present study analyzed data from the continuous NHANES 2007-2014. 1,0249 participants were enrolled in this study. Stratified by magnesium intake category (low-magnesium intake: <320mg/d; high=magnesium intake: >=320mg/d). We further evaluated the difference (interaction test) between the relationship of vitamin D and risk of T2D in low magnesium intake participants and high magnesium intake participants in the multivariable Logistic regression. Results: In this cross-sectional study, participants with high-intake magnesium were found to have a lower risk of T2D (15.0%vs19.0%, p<0.001). The association between serum vitamin D and risk of T2D appears to differ in the low magnesium intake group and the high magnesium intake group (OR: 0.99 95%Cl: 0.96-1.02 vs OR: 0.94 95%Cl: 0.90-0.99). Besides, there was evidence of interaction of vitamin D levels and magnesium intake on decreasing the incidence of T2D (p for interaction=0.018). Conclusions: Our study indicates that magnesium intake may affect the association between serum vitamin D with the risk of T2D, which requires further randomized controlled studies to provide more evidence.